2002 IEEE MTT-S International Microwave Symposium Digest (Cat. No.02CH37278)
DOI: 10.1109/mwsym.2002.1012293
|View full text |Cite
|
Sign up to set email alerts
|

An empirical HBT Large Signal Model for CAD

Abstract: Extensive measurements were performed at different temperatures on GaAs HBT's in order to obtain a simple Large Signal Model usable in CAD. The model was experimentally evaluated by DC, S and Power Spectrum measurements and good correspondence was obtained between measurements and experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…For user convenience, the capacitance model is arranged to have the same names and values for common parameters like MJC, VJC, but it is more stable in Harmonic Balance simulations. In this study, it was found that simpler depletion capacitance model C bedepl , C bcdepl , provides a good fit for actual devices and capacitance equations [23] are simplified as Eq. (2).…”
Section: Model Implementation In Adsmentioning
confidence: 91%
See 4 more Smart Citations
“…For user convenience, the capacitance model is arranged to have the same names and values for common parameters like MJC, VJC, but it is more stable in Harmonic Balance simulations. In this study, it was found that simpler depletion capacitance model C bedepl , C bcdepl , provides a good fit for actual devices and capacitance equations [23] are simplified as Eq. (2).…”
Section: Model Implementation In Adsmentioning
confidence: 91%
“…Following equations are proposed as extension of previously published HBT model [23], [24] and implemented in ADS to model the leakage:…”
Section: Leakage Temperature Dependencementioning
confidence: 99%
See 3 more Smart Citations